PENGARUH PEMBELAJARAN GAME ICE BREAKING TERHADAP MOTIVASI BELAJAR SISWA KELAS V (LIMA) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI 001 PANGKALAN KECAMATAN PUCUK RANTAU - As'ari As'ari; Sarmidin Sarmidin; Helbi Akbar (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2019)
This study aims to determine whether there is an effect of learning ice breaking game on student motivation and the factors that influence it on PAI subjects at SDN 001 PangkalanSubdistrict, PucukRantau. The population of this study was 28 students and one teacher. This research methodology is a type of quantitative data research with data collection techniques, namely: Observation, Interview, Documentation, and Questionnaire. The data analysis technique that I use is Simple Linear Regression. Based on the percentage achieved in this study it can be seen that the learning of ice breaking games in SDN 001 PangkalanRantau sub-district, using SPSS data processing. In SPSS, the significant value of the f test seen in anova output is known in the significant test of f count of 5.59% more than f table. Then the stipulation is if the value (Fcount) 32.963> (Ftable) 1.705 then Ho is rejected and Ha is accepted. It means that there is an effect of learning ice-breaking games on the learning motivation of fifth grade students at SDN 001 Kec, PucukRantau. The magnitude of the coefficient of determination (R square) of 0.559 is equal to 5.59%, this figure implies that the influence of ice breaking game learning on the motivation of fifth grade students of SDN 001 Pangkalan is 5.59%.